Efficacy and safety of autologous haematopoietic stem cell transplantation in systemic sclerosis: a systematic review of the literature. (1st March 2018) - Eyraud, A.; Scouppe, L.; Barnetche, T.; Forcade, E.; Lazaro, E.; Duffau, P.; Richez, C.; Seneschal, J.; Truchetet, M.‐E.; ,
Summary: We aimed to assess the efficacy of autologous haematopoietic stem cell transplantation (HSCT) for skin sclerosis (SSc) and lung function in SSc. We performed a systematic literature review in the PubMed and Scopus databases from the earliest records to March 2016. We assessed study quality using the Cochrane tool for randomized studies, the Newcastle–Ottawa Scale for controlled cohort studies and an 18‐item quality‐appraisal checklist for case series. The primary outcome was the improvement of skin thickening using the modified Rodnan Skin Score (mRSS). The secondary outcome was efficacy on lung function, using diffusing capacity of the lungs for carbon monoxide and forced vital capacity (FVC). The safety of the procedure was evaluated. The literature search identified 431 citations. There were 38 studies involving a total of 344 patients who fulfilled our inclusion criteria. No meta‐analysis was performed due to a high heterogeneity. There was a significant improvement in mRSS in the majority of the reports ( P < 0·05), and the results were sustained for up to 8 years after autologous HSCT. The randomized studies and the four cohort studies each showed a slight but statistically significant improvement in FVC at 1 or 2 years. The treatment‐related mortality calculated by pooling patients of 35 studies (336 patients with a follow‐up up to 146 months) was 8·3% after autologous HSCT and 1% in cyclophosphamide‐treated groups. Despite heterogeneity among the studies, we determined that autologous HSCT significantly improved cutaneous fibrosis and slightly improved FVC. Safety of autologous HSCT is acceptable given the severity of the disease. This systematic review was registered on PROSPERO, number CRD42016027951.